(untitled) (Conference on English Language Teaching, 2025)
The transformation of Indonesian language learning on Narrative Text material at the junior high school level requires media innovation that is in accordance with the characteristics of the digital native generation. This research aims to describe the utilization of digital comics based on artificial intelligence (AI) in learning Narrative Text. The method used is a literature study with a descriptive-qualitative approach, reviewing literature and scientific articles related to the utilization of digital comics and AI in language learning. The results showed that AI-based digital comics have benefits in increasing learning motivation, facilitating understanding of narrative text structures, and training students’ creative writing and digital literacy skills. However, its implementation faces challenges, such as limited access to technology, variations in digital literacy skills of teachers and students, and the need to review the quality of automated content. Therefore, a development strategy is needed through teacher training, strengthening students’ digital literacy, and developing contextual local content. The utilization of AI-based digital comics is expected to transform narrative text learning to be more interesting, effective, and relevant to the demands of the 21st century.